Leveraging Social Media Engagement for Business Growth: Insights into Brand Awareness and Customer Loyalty in Human Resource Management - Hardinalis Kobal (Lembaga Pengembangan Kinerja Dosen, 2025)
This research explores the effects of digital marketing strategy, pricing, and product quality on the sales performance of Rendang Cipuik GG, a traditional culinary SME based in Lima Puluh Kota Regency, Indonesia. Employing a quantitative explanatory approach, data were gathered from 100 consumers using structured questionnaires and analyzed through multiple regression alongside SEM-PLS techniques. The analysis demonstrates that digital marketing and product quality exert significant positive influences on sales performance, whereas pricing shows no substantial effect. Nonetheless, the joint analysis reveals that all three variables, when considered simultaneously, contribute to shaping sales outcomes.The findings emphasize that in heritage-based culinary industries, consumers are more inclined to value authenticity, taste consistency, and overall product excellence rather than price competitiveness. This result highlights the pivotal role of digital transformation for SMEs, particularly in leveraging online platforms to expand market reach and strengthen brand presence. By maintaining high-quality standards while embracing digital channels, SMEs can sustain competitiveness and secure consumer loyalty in an increasingly digital economy. From a theoretical standpoint, this study enriches the existing body of SME marketing literature by presenting a comprehensive model that integrates digital marketing, pricing, and product quality into one framework. It adds empirical evidence supporting the primacy of non-price factors in shaping sales dynamics within traditional food businesses. Practically, the research offers actionable insights for SME owners and managers: prioritizing investment in digital marketing initiatives and ensuring consistent product quality should be the cornerstone of competitive strategies. Ultimately, the study illustrates that heritage-based SMEs must align tradition with innovation to remain sustainable and profitable in the digital era.